2021
DOI: 10.1109/tbme.2020.3030892
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Focused Ultrasound Neuromodulation of Voluntary Movement-Related Cortical Activity in Humans

Abstract: Transcranial focused ultrasound (tFUS) is an emerging non-invasive brain stimulation tool for safely and reversibly modulating brain circuits. The effectiveness of tFUS on human brain has been demonstrated, but how tFUS influences the human voluntary motor processing in the brain remains unclear. Methods: We apply low-intensity tFUS to modulate the movement-related cortical potential (MRCP) originating from human subjects practicing a voluntary foot tapping task. 64channel electroencephalograph (EEG) is record… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Through ESI, the results showed that tFUS modulates MRCP source dynamics with high spatiotemporal resolutions and significantly increases the MRCP source profile amplitude (MSPA), and further, a high PRF enhances the MSPA outperforms a low UPRF does. This study provides the first evidence that tFUS enhances human endogenous motor cortical activities through excitatory modulation ( Yu et al, 2020 ).…”
Section: Excitatory Modulationmentioning
confidence: 86%
See 2 more Smart Citations
“…Through ESI, the results showed that tFUS modulates MRCP source dynamics with high spatiotemporal resolutions and significantly increases the MRCP source profile amplitude (MSPA), and further, a high PRF enhances the MSPA outperforms a low UPRF does. This study provides the first evidence that tFUS enhances human endogenous motor cortical activities through excitatory modulation ( Yu et al, 2020 ).…”
Section: Excitatory Modulationmentioning
confidence: 86%
“…As discussed by the authors, the different findings may be caused by stimulation parameters and other methodological factors. Yu et al (2020) demonstrated the neuromodulatory effects of low-intensity tFUS on human voluntary movement-related cortical potential (MRCP). Through ESI, the results showed that tFUS modulates MRCP source dynamics with high spatiotemporal resolutions and significantly increases the MRCP source profile amplitude (MSPA), and further, a high PRF enhances the MSPA outperforms a low UPRF does.…”
Section: Excitatory Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sound pressure was chosen based on the literature on tFUS neuromodulation. For example, Yu et al (2020) select a sound pressure of 0.8092 MPa in their experiment. Sound pressures of 0.5, 1, 2, and 4 MPa are used in another study ( Gaur et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Using a simultaneous ultrasound and TMS paradigm, LIFU to the motor cortex ( Table 1 ) reduced the amplitude of TMS-evoked motor evoked potentials and attenuated intracortical facilitation ( 31 ). Conversely, a study using concurrent LIFU-EEG ( Table 1 ), found evidence that LIFU enhanced the movement-related cortical potential ( 33 ). A novel theta burst patterned LIFU protocol was also recently introduced that produced a consistent increase in motor cortical excitability ( 35 ).…”
Section: Ultrasound Neuromodulation In Humansmentioning
confidence: 99%